Computer forensies : jumpstart - Solomon, Michael [ (Michael G.)] , 1963- (Indianapolis, Indiana : Wiley Publishing, 2011)
A guide to computer forensics provides information on such topics as conducting a forensics investigation, finding hidden data, capturing images, collecting and preserving computer evidence, and using computer forensic tools.
1. The need for computer forensics -- 2. Preparation -- what to do before you start -- 3. Computer evidence -- 4. Common tasks -- 5. Capturing the data image -- 6. Extracting information from data -- 7. Passwords and encryption -- 8. Common forensics tools -- 9. Pulling it all together -- 10. How to testify in court
Previous ed.: San Francisco, Calif.; London: SYBEX, 2005
Includes bibliographical references (p. 271-281) and index
Keywords: Computer crimes -- Accidents -- Investigation; Computer networks -- Security measures; Computer security; Forensic sciences